KEMAMPUAN MENYIMAK BERITA DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL SISWA KELAS VII DI SMP NEGERI 1 ULUSUSUA - Mei Hati Ndruru (LPPM Universitas Nias Raya, 2023)
This research was motivated by a problem, namely the low ability to listen to the news of grade VII students, there are still students underestimating listening learning, subject teachers rarely use audiovisual media when listening learning. The purpose of this study is to describe the ability to listen to news using audiovisual media of grade VII students at SMP Negeri 1 Ulususua Learning Year 2022/2023. The population and sample of this study were all grade X students of SMK Negeri 1 Toma totaling 23 people. The result of this study is that all grade VII students Learning Year obtained an average score of 75.25 with the category of quite good in listening to news texts, thus in the ranks of aspects in listening to the news obtained low average scores such as in what aspect, whose aspect, which aspect, when aspect, why aspect, what aspect. The suggestion of this study is (a) Students should improve the habit of listening to the news, because this habit can be started by listening to the news, listening to a movie, or listening to news about events at school. (b) For Indonesian teachers: Teachers who teach Indonesian subjects are expected to provide knowledge about listening to news to students clearly and completely.